This preview shows page 1. Sign up to view the full content.
Unformatted text preview: D = C-1 B-1 A-1 . Then D ( ABC ) = C-1 B-1 ( A-1 A ) BC = C-1 B-1 ( I n ) BC = C-1 ( B-1 B ) C = C-1 ( I n ) C = C-1 C = I n and ( ABC ) D = AB ( CC-1 ) B-1 A-1 = AB ( I n ) B-1 A-1 = A ( BB-1 ) A-1 = A ( I n ) A-1 = AA-1 = I n . i.e., D ( ABC ) = I n = ( ABC ) D . Thus, ABC is invertible and D = C-1 B-1 A-1 is the inverse. 1...
View Full Document
This note was uploaded on 04/23/2008 for the course MATH 227 taught by Professor Sze during the Fall '06 term at UConn.
- Fall '06